Development Strategies Analysis Using the SCOR Method Approach: A Case Study from Medical Device Company - Evan Nugraha; Rini Mulyani Sari; Arief Yunan (Universitas Airlangga, 2022)
Objective: This study aims to measure the performance of supply chain management at PT. Multi Anugrah Satu identifies supply chain management activities that require improvement and provides recommendations for improving performance strategies in supply chain management activities Design/Methods/Approach: The initial stage of this study is to determine KPI and scores for the weighting of the COR and AHP methods, which respondents fill in, then the data are processed and identified using OMAX and the Light System in measuring the improvement of SCM performance management at PT. Anugrah Satu. Findings: Using the SCOR method the firm obtains 83.48 out of 100. The value suggests a need for strategy that focuses more on decision-making at the management level and in the long term. Originality: This study develops strategic operation management science and help improve public health levels during the COVID-19 pandemic. Practical/Policy implication (optional): The implications of supply chain management strategies for management and business practices are developing advanced logistics management as a strategy to increase competitive advantage for the company.